2020
DOI: 10.1002/bjs.11587
|View full text |Cite
|
Sign up to set email alerts
|

Consensus on definition and severity grading of lymphatic complications after kidney transplantation

Abstract: Background: The incidence of lymphatic complications after kidney transplantation varies considerably in the literature. This is partly because a universally accepted definition has not been established. This study aimed to propose an acceptable definition and severity grading system for lymphatic complications based on their management strategy. Methods: Relevant literature published in MEDLINE and Web of Science was searched systematically. A consensus for definition and a severity grading was then sought be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 94 publications
(128 reference statements)
0
17
0
1
Order By: Relevance
“…The formation of lymphatic fistula after RT is a common complication occurring in up to 20% of the cases [96][97][98], caused by dissection of lymphatic vessels of the donor kidney during preparation and recipient pelvis during allograft implantation. Data indicates that the use of an absorbable polysaccharide hemostatic powder (HaemoCer™) can reduce the incidence of lymphatic fistula [99].…”
Section: Lymphatic Fistulamentioning
confidence: 99%
“…The formation of lymphatic fistula after RT is a common complication occurring in up to 20% of the cases [96][97][98], caused by dissection of lymphatic vessels of the donor kidney during preparation and recipient pelvis during allograft implantation. Data indicates that the use of an absorbable polysaccharide hemostatic powder (HaemoCer™) can reduce the incidence of lymphatic fistula [99].…”
Section: Lymphatic Fistulamentioning
confidence: 99%
“…Lymphoceles can lead to further complications, such as impaired wound healing, thrombosis, and organ failure. The reported incidences of lymphoceles after KTx vary widely (from 0.6% to 51%) [ 2 , 3 , 4 ]. This vast discrepancy in the reported incidences can be attributed to the lack of a standardized definition for post-KTx lymphatic complications but also to differences in the means of routine postoperative diagnosis and distinct follow-up protocols [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mehrabi et al addressed the lack of an objective definition for lymphoceles that follow KTx [ 4 ] in a systematic review that evaluated existing definitions and suggested a consensus-defined severity grading for post-KTx lymphoceles. They found that lymphoceles were defined as a fluid collection of any size near the transplanted kidney after urinoma, hematoma, and abscess were excluded.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations